Sucrose supplements in cattle given grass silage-based diet. 2. Digestion of cell wall carbohydrates - Khalili, H.; Huhtanen, P. (Elsevier, 1991)
In a 4 X 4 Latin square experiment, 4 male Friesian cattle with rumen and duodenal cannulae were given a basal diet of grass silage 700, barley 240 and rapeseed meal 60 g/kg total DM at the rate of 5.3 kg DM/day (diet C) or supplemented with sucrose 1.0 kg/day given twice daily (diet S), twice daily with sodium bicarbonate 0.25 kg/day (diet B) or as a continuous intraruminal infusion (diet I). Duodenal flow of neutral detergent fibre (NDF), acid detergent fibre (ADF), cellulose and hemicellulose was estimated using chromium mordanted straw and Co-EDTA. Degradation characteristics of silage DM, NDF and ADF were studied by incubating samples in nylon bags in the rumen for different periods. Sucrose supplements increased duodenal flow of NDF (P 0.1), ADF (P 0.05), cellulose (P 0.05) and hemicellulose (P 0.01) compared with diet C. In spite of partial compensation for reduced rumen digestion in the hindgut, total digestibility of cell wall carbohydrates decreased when sucrose was given. Among the sucrose diets, bicarbonate supplement reduced the adverse effect of sucrose on fibre digestion and the values for diet B were similar to those for diet C. Continuous infusion of sucrose had a similar adverse effect on fibre digestion to diet S. Diets S and I decreased disappearance of silage DM, NDF and ADF from nylon bags, especially after incubation periods of 12-48 h, and as a result the rate constants for the degradation of different silage components were lower (P 0.05) than with diets C and B. Sucrose supplements increased the lag time of fibre digestion.